The Effect of Auxin and Gibberellin Combination on the Growth and Parthenocarpy of Eggplant (Solanum melongena var. Gelatik) - Nurita, Febrilia Dwi; Yuliani, Yuliani (LenteraBio : Berkala Ilmiah Biologi, 2023)
Eggplant is fruiting vegetable with high demand but not balanced with maximum production because poor productivity. The purpose of this study was to determine the effect of auxin and gibberellin on growth and parthenocarpy in eggplants. This research was experimental using Randomized Block Design with two treatment type and concentration of hormone and 4 levels of hormone, 100 ppm, 300 ppm, 500 ppm and 700 ppm. This research was conducted on 45 samples with 3 replications. The data collected at 75 DAP on plant height, stem diameter, leaves number, leaf area, flowers number, wet weight, root length and parthenocarpy including fruit weight and seeds number. The results showed that application of auxin and gibberellin hormones had significant effect on plant height, number of leaves, leaf area, number of flowers and fresh weight but did not have the significant effect on stem diameter and length of the roots. The best treatment was auxin 100 ppm and gibberellin 100 ppm with average plant height of 50.00; stem diameter 5.83; leaves number 48.67; leaf area 94.27; flowers number 14.68; root length 18.10; wet weight 36.00; and fruit weight 2.83. The best treatment for seeds number was gibberellins 700 ppm with average result of 43.33.